STRATEGI PENINGKATAN LITERASI DAN INKLUSI KEUANGAN BAGI MASYARAKAT AGRARIS DI KAWASAN PEDESAAN - Mirdha Fahlevi SI; Yusnaidi Yusnaidi; Amsal Irmalis (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2021)
The government’s objective to increase financial literacy and inclusion should be supported by the stakeholders. The increasing of financial inclusion and literacy play important role to generate community livelihood. Currently, the level of financial inclusion and literacy in Indonesia are diverse. It depends on many factors such as where they are living, in urban area or country site. In urban areas, the financial literacy index reaches 41.41 percent and the level of financial inclusion reaches 83.60 percent. On the other hand, in rural areas the financial literacy index only 34.53 percent and the level of financial inclusion only reaches 68.49 percent. These statistics information show the lack of financial inclusion and literacy among rural community who most of them work as farmers and fishermans. Therefore this research is conducted through desk research methods to examine factors which cause the lack of financial inclusion and literacy within agrarian society. The research offers the strategic plan to improve  financial inclusion and literacy index within three years period, which are devided into three phases. The first one is called as the phase of educating coomunity, the second phase is the penetration of financial institution and the last phase is expanding the access of financial services to the agrarian society. This road map is one of the alternative strategy that could be adopt to improve the financial inclusion and literacy and to support government development program.Keywords: Financial Literacy, Financial Inclusion, Agrarian Society.